PREDICTORS OF THE DEVELOPMENT OF ARTERIAL HYPERTENSION IN 6-MONTH-OLD CHILDREN BORN AT VERY EARLY PRETERM BIRTH - Захарова, Светлана Юрьевна; Покусаева, Оксана Сергеевна (Mother and Baby in Kuzbass, 2024)
Introduction. Children born at the time of early preterm labor (SPR) are a group at high risk of developing cardiovascular diseases, including hypertension, which can occur throughout life. To date, there is a need to determine the diagnosis, develop a follow-up plan for this category of children. The aim of the research is to identify predictors (factors) of the occurrence of arterial hypertension in young children born at the time of early preterm labor. Materials and methods. We examined 58 premature babies at the age of 6 months. The main group consisted of 36 children who were born as a result of early preterm labor. This group was divided into 2 subgroups. The first subgroup included children with a weight in the range from 500 to 750 g (n = 12), and the second subgroup included children whose birth weight was more than 751 g (n = 24). The comparison group (n = 22) consisted of children born at 32-35 weeks gestation. The indicators and parameters of blood pressure and the levels of renin, angiotensin II were evaluated. Results. In young children born at the time of early preterm labor, high blood pressure indicators were detected. Arterial hypertension was diagnosed in the main group. The results of laboratory studies showed a statistically significant increase in the level of renin and angiotensin II in venous blood in children of the main group than in children of the comparison group. Conclusion. In our study, it was revealed that chronic fetoplacental insufficiency in the mother, ante- and intranatal hypoxia are possible risk factors that program the implementation of arterial hypertension in the subsequent life of the child. Premature babies born at the time of early preterm labor need to develop individual diagnostic and dispensary monitoring programs in order to identify potential risks of hypertension early.